The Role Of Vitamin D And Calcium In Pre-Eclampsia And The Association With Neonatal Outcomes - Fadila, Tara; Yusrawati, Yusrawati; Karmia, Hudila Rifa (Andalas Obstetrics And Gynecology Journal, 2023)
Introduction: Pre-eclampsia is one of the main causes of maternal and neonatal death in developingcountries. A low vitamin D level can increase the risk of neonatal abnormalities. Clinical studiesreported various complications of low vitamin D levels, such as pre-eclampsia, gestational diabetes,low birthweight, and caesarean section. This study aimed to investigate the role of vitamin D inpregnancy with pre-eclampsia and its association with neonatal outcomes.Methods: This is an observational analytical study uses a cross-sectional approach to investigatevitamin D levels and pre-eclampsia, conducted in General Hospital Dr. M. Djamil Padang from Mei2021 – April 2022. A total of 5 mL blood was withdrawn to analyzed vitamin D. This study has beenapproved by Health Research Ethics Committee Andalas University (Approved number:339/KEPK/2021).Results: There was a significant difference in the levels of 1,25 dihydroxy vitamin D3 between normalpregnancy and pre-eclampsia patients (99,18 vs 72,53 pg/ml; p = 0,033). In the pre-eclampsia patients’first APGAR score, there was a significant difference in the levels of 1,25 dihydroxy vitamin D3 betweennormal, moderate, and severe asphyxia groups (114,19 vs 66,75 vs 74,78 pg/ml; p = 0,025).Conclusion: Measuring early maternal 1,25 dihydroxy vitamin D3 can lower the pre-eclampsia risksand the impact the perinatal outcomes, particularly in determining first Apgar scores.